Duluth, Pottawatomie County - Hahn, Shane (Kansas State University, The Chapman Center for Rural Studies, 2011)
The end of Duluth Town Company came before its twenty-year charter expired. In February of 1912, the directors voted to decrease its capital stock and, three years later, to liquidate all of its assets. The company was officially dissolved on February 20, 1915.5 Just because the Duluth Town Company is no longer in existence, does not mean that the town died. The church still holds services every week and there are many people who still call the area home.
Shane Hahn, “Duluth, Pottawatomie County,” Chapman Center Research Collections, accessed October 21, 2020, https://ccrsresearchcollections.omeka.net/items/show/52.
Keywords: Duluth; Mill Creek Township; Pottawatomie County; St. Pauls Lutheran Church; William Kolterman; Shane Hahn